PERAN DOSEN DIGITAL IMMIGRANT DALAM KOMUNIKASI VIRTUAL - Dewi Fayruz Safitri; Sugeng Pradikto (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Using a case study at Universitas PGRI Wiranegara (UNIWARA), this study tries to find out the function of digital immigrant instructors in virtual communication. According to Marc Prensky's theory, this study uses a qualitative descriptive method with lecturer informants born before 1980 and involves students as source triangulation. Snowball sampling was the method used in this study, and data literacy and interviews were used for data collection. According to the study's findings, Zoom and WhatsApp are the most commonly used virtual communication platforms among digital immigrant professors. By raising courses that are relevant to the professional background of the participants, reviewing case studies of problems in the workplace related to communication science theory, and evaluating the effectiveness of communication by examining the results of assignments or students' reactions to the content and discussions in online lectures, lecturers can attract students to participate.